2008
DOI: 10.1111/j.1468-4446.2007.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Being a pretty good citizen: an analysis and monetary valuation of formal and informal voluntary work by gender and educational attainment1

Abstract: This paper is set in the context of macrosocial/macroeconomic theories of the organization of both paid and unpaid work. The specific topic investigated is engagement in unpaid voluntary work, an activity which is thought to be important for social cohesion, civil society and citizenship. Research on the sources of social cohesion has focused on organizational membership and voluntary organization activity. There has been little investigation of informal helping of non-resident kin, friends or acquaintances, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…At the individual level, gender, age, health, income, educational level, marital status, presence of children in the household, and employment status have been found to influence informal volunteering, so we include them as controls. Earlier studies have found that women do more informal volunteering than men (Egerton and Mullan 2008;Gundelach, Frietag, and Stadelmann-Steffen 2010;Hank and Stuck 2008;Hook 2004). Informal volunteering increases with age and then declines late in life as health declines (Gundelach, Frietag, and Stadelmann-Steffen 2010).…”
Section: Independent Variablesmentioning
confidence: 99%
“…At the individual level, gender, age, health, income, educational level, marital status, presence of children in the household, and employment status have been found to influence informal volunteering, so we include them as controls. Earlier studies have found that women do more informal volunteering than men (Egerton and Mullan 2008;Gundelach, Frietag, and Stadelmann-Steffen 2010;Hank and Stuck 2008;Hook 2004). Informal volunteering increases with age and then declines late in life as health declines (Gundelach, Frietag, and Stadelmann-Steffen 2010).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The UK evidence demonstrates that middle‐class people are more likely to be in groups and engage in formal voluntary activity (Egerton 2002; Li et al . 2003; Egerton and Mullan 2008). Evidence in relation to both the USA and England demonstrates how more geographically mobile middle‐class mothers, in particular, rely on groups such as parents' groups to make friendship networks in new neighbourhoods (McGrath and Kuriloff 1999; Bagnall et al .…”
Section: Causal Theories and Evidencementioning
confidence: 99%
“…creates social groups within society), whereas formal volunteering tends to ‘bridge’ social capital (i.e. creating societal social capital) (Egerton & Mullan ). Volunteers in EOLC services are often seen as having social proximity to the people who use services and thus may be an important factor in creating societal ‘capital’ by embedding services in the community (Hill et al .…”
Section: Introductionmentioning
confidence: 99%